2020
DOI: 10.1111/gcb.15437
|View full text |Cite
|
Sign up to set email alerts
|

Global soil‐derived ammonia emissions from agricultural nitrogen fertilizer application: A refinement based on regional and crop‐specific emission factors

Abstract: Ammonia (NH3) emissions from fertilized soils to the atmosphere and the subsequent deposition to land surface exert adverse effects on biogeochemical nitrogen (N) cycling. The region‐ and crop‐specific emission factors (EFs) of N fertilizer for NH3 are poorly developed and therefore the global estimate of soil NH3 emissions from agricultural N fertilizer application is constrained. Here we quantified the region‐ and crop‐specific NH3 EFs of N fertilizer by compiling data from 324 worldwide manipulative studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(59 citation statements)
references
References 52 publications
2
56
1
Order By: Relevance
“…To estimate the relative contribution of China's cropland Nr emissions to the global GTP from agricultural N fertilizer use, we used the data on global cropland Nr emissions that were estimated based on the direct EFs established from two recent worldwide assessments (Liu et al, 2017;Ma et al, 2021). The results showed that China contributed to 33% and 31% of the global croplands GTP 20 and GTP 100 , providing that global croplands GTP 20 and GTP 100 from showing a better agreement with a previous analysis that suggested that climate change could regulate soil N availability via mineralization by soil microorganisms (Liu, Vitousek, et al, 2016;Liu, Wang, et al, 2016).…”
Section: Climate Change Impacts Of Cropland Nr Emissions In Chinamentioning
confidence: 99%
“…To estimate the relative contribution of China's cropland Nr emissions to the global GTP from agricultural N fertilizer use, we used the data on global cropland Nr emissions that were estimated based on the direct EFs established from two recent worldwide assessments (Liu et al, 2017;Ma et al, 2021). The results showed that China contributed to 33% and 31% of the global croplands GTP 20 and GTP 100 , providing that global croplands GTP 20 and GTP 100 from showing a better agreement with a previous analysis that suggested that climate change could regulate soil N availability via mineralization by soil microorganisms (Liu, Vitousek, et al, 2016;Liu, Wang, et al, 2016).…”
Section: Climate Change Impacts Of Cropland Nr Emissions In Chinamentioning
confidence: 99%
“…As a result, it really depends which soil properties are being used in the application. Therefore, the choice of database and the evaluation of the database depends whether one is studying soil erosion [39], soil salinity [40], ammonia emissions [41], crop growth [42], or Carbon stocks [43] The study confirmed the importance of soil legacy data rescue [44] and global soil profile databases like WoSIS, as well as the necessity of the global soil community to invest in this kind of initiative.…”
Section: Discussionmentioning
confidence: 67%
“…A clearer picture can be derived about the interplay of stomatal (Geßler et al, 2002) and non-stomatal pathways (Schrader et al, 2016), the exchange between soil and the atmosphere, seasonal site-specific conditions, e.g., through vegetation senescence and decomposition of fallen leaves (Hansen et al, 2013) or periods of elevated evaporation from either water droplets on leaves (Hales and Drewes, 1979) or whole water bodies. Furthermore, although not presented in this study, short-term temporal dynamics of Nr after field management like crop or grassland fertilization usually leading to immediate emission peaks (Martins et al, 2017) can be used for better quantification of nitrogen losses to the atmosphere (Brümmer et al, 2013;Ma et al, 2020).…”
Section: Improving Process Understanding Through High Temporal Resolutionmentioning
confidence: 99%